Forensic psychology and its relationship to sexual abuse children and teenagers (Research, Society and Development, 2020)
In recent years, there has been an increase in the spread of cases of violence and abuse against the juvenile population, with sexual abuse being one of the most common in this life cycle. Based on this explanation, this paper aims to verify the relationship and importance of forensic psychology in crimes of sexual abuse against children and adolescents. This article is a narrative review, covering scientific articles, monographs, theses and dissertations published in the databases: CAPES, SciELO and Google Scholar. Through studies, it appears that the professional psychologist among numerous functions, highlights and analyzes the psychological aspects of the people involved, hidden behind procedural relationships. The main purpose of psychological expertise is to assist the judge in making a decision, thereby ensuring the rights and welfare of the child and / or adolescent. Finally, it is concluded that the main objective of the study can be achieved, referring to the analysis of the relationship between forensic psychology and children and adolescents victims of sexual abuse.